Antibacterial Screening Activity of Several Sponges Against Staphylococcus aureus, Escherichia coli, Staphylococcus saprophyticus, dan Pseudomonas aeruginosa - Deiske A. Sumilat (Sam Ratulangi University, 2019)
Sponge samples collected around Manado waters were obtained 30 species and their crude extracted have been tested in vitro for their activity in inhibiting bacterial growth. Based on the results of antibacterial screening in 30 sponge extracts, there were 23 sponge extracts which had bioactivity in inhibiting the growth of S. aureus, E. coli, S. saprophyticus and P. aeruginosa, Sponge extract No. 43 (of 30 sponge extracts tested) was the most active in inhibiting bacterial growth and had the widest inhibition zone diameter.Keywords: screening, sponge, crude extract, antibacterial, ManadoABSTRAKSampel spons dikoleksi di sekitar Perairan Manado sebanyak 30 jenis/spesies, dimana ekstrak kasarnya telah diuji secara in vitro aktivitasnya dalam menghambat pertumbuhan bakteri. Berdasarkan hasil skrining antibakteri pada 30 ekstrak spons didapatkan hasil ada 23 ekstrak spons yang mempunyai bioaktivitas dalam menghambat pertumbuhan bakteri S. aureus, E. coli, S. saprophyticus dan P. aeruginosa, Ekstrak spons No. 3 (dari 30 ekstrak spons yang diuji) adalah yang paling aktif dalam menghambat pertumbuhan bakteri dan memiliki diameter zona hambat yang paling lebar.Kata kunci: skrining, spons, ekstrak kasar, antibakteri, Manado